UPAYA MELESTARIKAN BAHASA SASAK MELALUI MENDONGENG CERITA-CERITA SUKU SASAK DI TPQ DESA SETILING - Wahidah, Baiq Yulia Kurnia; Putra, Agus Darma; Rahman, Saeful; Yulandari, Evy Safitri (LPPM Institut Pendidikan Nusantara Global, 2024)
Storytelling is one of the media for preserving culture and language that can be developed. One of the Sasak tribe's folktales often used as storytelling material include Putri Mandalika, Tegodek-Godek, and Tuntel. This study aims to describe the use of storytelling in the Qur’anic Learning Center (TPA) located in Setiling Village. Using a qualitative descriptive method, the study reveals that Sasak folktales are utilized by teachers as material for storytelling activities in the TPA. Additionally, the study highlights the benefits of storytelling in increasing students' reading interest, particularly in Sasak folktales. Through storytelling, students not only receive entertainment but also learn about cultural values embedded in the stories. This activity introduces and preserves local culture among the younger generation, supports literacy development, and fosters an early appreciation for the richness of regional heritage, making storytelling an effective method for combining education and cultural preservation..